2017
DOI: 10.1108/ijbm-03-2016-0041
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive hierarchical model of retail banking

Abstract: Purpose The purpose of this paper is to develop and test a comprehensive hierarchical model of behavioural intentions in the Malaysian retail banking industry. Design/methodology/approach The data were analysed using EFA, CFA and structural modelling. Findings The findings illustrate that customer satisfaction is the most important determinant of behavioural intentions, followed by switching costs, corporate image and perceived value. Service quality is indirectly related to behavioural intentions and cust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
76
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(95 citation statements)
references
References 92 publications
(127 reference statements)
10
76
0
9
Order By: Relevance
“…9 Most recent academic papers use hierarchical models when dealing with multilevel cross-country data (e.g., Bakar et al, 2017;Dong and Stettler, 2011;Kayo and Kimura, 2011;Ketelhöhn and Quintanilla, 2012;Li et al, 2013;Mihet, 2013). However, it is also common to run OLS regressions with country and/or firm dummies, to capture country/firm time-invariant (fixed) effects.…”
Section: Methodsmentioning
confidence: 99%
“…9 Most recent academic papers use hierarchical models when dealing with multilevel cross-country data (e.g., Bakar et al, 2017;Dong and Stettler, 2011;Kayo and Kimura, 2011;Ketelhöhn and Quintanilla, 2012;Li et al, 2013;Mihet, 2013). However, it is also common to run OLS regressions with country and/or firm dummies, to capture country/firm time-invariant (fixed) effects.…”
Section: Methodsmentioning
confidence: 99%
“…Scholars have now spent a considerable amount of time debating the concept of service quality, and after several decades, most define it as a comparative judgment of perceived expectations-actual service performance (Parasuraman et al, 1985); it is likely that this is positively associated with customer loyalty (Bakar et al, 2017;Hapsari et al, 2017;Yilmaz et al, 2018). Bakar et al (2017) argued that service quality, although exerting no significant impact on behavioral intentions, is the prime determinant of customer satisfaction, followed by switching costs, corporate image, and perceived value. Wang (2010) also reports that service quality is a strong predictor of customer loyalty, while Sigit (2018) asserts it is an important influence on customer satisfaction, retention, and loyalty.…”
Section: Service Qualitymentioning
confidence: 99%
“…In fact, numerous studies have proved that service quality is the principal factor in customer loyalty (Bakar, Clemes, & Bicknell, 2017;Sigit, 2018;Yilmaz, Ari, & Gürbüz, 2018;Zeithaml, Bitner, & Gremler, 2018), as well as a strategic tool for achieving excellence in service performance (Zeithaml et al, 2018) and acquiring a competitive advantage (Ladhari, Ladhari, & Morales, 2011). Ladhari et al (2011) found that a 5% increase in customer retention led to a 25%-85% increase in profits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Religion shows its followers in the form of a series of beliefs, impressions, and values in interacting with certain communities(Mathras et al, 2016). Religiosity is defined as a person's level of trust and obedience to God accompanied by a commitment to follow the principles adopted through religious practices in everyday life(Mansour & Diab, 2016;Bakar et al, 2017;Nurhayati & Hendar, 2019). In other words, religiosity is an indication of someone to choose and consume a product that is in accordance with the principles of their religion (Mathras et al, 2016; Suhartanto et al, 2019).In Islam, the level of religiosity, in general, can be assessed with the frequency of someone to pray and worship in accordance with the principles of the teachings of Islam(Nurhayati & Hendar, 2019).…”
mentioning
confidence: 99%